Public Perception of Polda Bengkulu in Handling Covid-19 Pandemic - Risdianto, Risdianto; Hayu, Rina Suthia; Abdillah, Willy (Indonesian Journal of Multidisciplinary Science, 2023)
The research aims to know the role of the Bengkulu Regional Police the Stigma of the Bengkulu Province Community towards the Police, especially the Bengkulu Regional Police, the right role to change the Bengkulu Province Community Stigma through the role of the Bengkulu Regional Police Biddokes, and the ability of the Bengkulu Police Health Workers in becoming Soft Weapons for the Police Institution as well as know the right model to change the Stigma of the Bengkulu Province Community towards the National Police, especially the Bengkulu Regional Police in handling the Covid 19 Pandemic. The research design used was descriptive and qualitative. A sample of 90 people was taken by accidental sampling. Data analysis was carried out descriptively and qualitatively. The results showed: The role of the Bengkulu Regional Police in handling the Covid 19 Pandemic was in the very good category, The stigma of the Bengkulu Province Community towards the Police is in a good category, The right role to change the Stigma of the Bengkulu Province Community through the role of the Bengkulu Regional Police Biddokes is in a good category,  Ability Bengkulu Police Health Workers in becoming Soft Weapons for Police Institutions in the very good category because the Bengkulu Police Health Workers have devoted and dedicated all their capabilities to serve the community, and The right model to change the Stigma of the Bengkulu Province Society towards Polri is through the framing method to package more interesting messages or information for the community.